Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376262
|View full text |Cite
|
Sign up to set email alerts
|

Button Simulation and Design via FDVV Models

Abstract: Designing a pushbutton with desired sensation and performance is challenging because the mechanical construction must have the right response characteristics. Physical simulation of a button's force-displacement (FD) response has been studied to facilitate prototyping; however, the simulations' scope and realism have been limited. In this paper, we extend FD modeling to include vibration (V) and velocity-dependence characteristics (V). The resulting FDVV models better capture tactility characteristics of butto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Among these methods, the FD curve is often used as a preliminary way of considering force feedback delivered by a mechanism that displaces with one degree of freedom (e.g. buttons and knobs) [6,14,16,34,36]. It is important to note that the FD curve does not comprehensively communicate all the haptic nuances of interacting with a physical input.…”
Section: Quantifying Haptic Force Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these methods, the FD curve is often used as a preliminary way of considering force feedback delivered by a mechanism that displaces with one degree of freedom (e.g. buttons and knobs) [6,14,16,34,36]. It is important to note that the FD curve does not comprehensively communicate all the haptic nuances of interacting with a physical input.…”
Section: Quantifying Haptic Force Feedbackmentioning
confidence: 99%
“…It is important to note that the FD curve does not comprehensively communicate all the haptic nuances of interacting with a physical input. For instance, static FD calculations do not capture changes due to different interaction velocities and they do not account for vibrations (cutaneous stimulation) that participate in the haptics [16]. However, for designers unfamiliar with haptics, FD curves offer an approachable way to consider the haptics of physical inputs; such as the "click" of a button [2,14], or the stops along a knob's rotation [37].…”
Section: Quantifying Haptic Force Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazursky et al [52] demonstrated a thin, button-type actuator based on ER fluid. Designing button-type actuators has long been studied in human-computer interaction, but often requires combining separate actuators for each sensation or convincing the user of displacement through haptic illusions [53][54][55]. In contrast, using smart fluids enables a single mechanism for providing both sensations.…”
Section: Introductionmentioning
confidence: 99%
“…This limits its versatility as a programmable, informative, or affective interface. A natural idea to improve this drawback is adding a force actuator, e.g., a linear motor, to a physical button and modulating its kinesthetic response [34,35,56]. When implemented appropriately, this approach provides physically faithful sensations and pleasant experiences.…”
Section: Introductionmentioning
confidence: 99%